Neurodegeneration in Ataxia Telangiectasia: What Is New? What Is Evident? - Hoche, Franziska; Seidel, Kay; Theis, Marius; Vlaho, Stefan; Schubert, Ralf; Zielen, Stefan; Kieslich, Matthias (Neuropediatrics, 2012)
This article summarizes evident and recent findings on the characteristics of the neurological phenotype in ataxia telangiectasia (AT), reviews neuropathological and neuroradiological findings, and outlines therapeutic treatment options. In addition, this review offers an overview of current hypotheses on mechanisms of neurodegeneration in AT and discusses their relevance in clinical neurology. The obvious features of neurodegeneration in AT—cerebellar ataxia and dysarthia—are accompanied by a variety of further disabling disease symptoms. Review of the literature outlines a complex pattern of central nervous degeneration in AT that might have been underestimated so far. Neurodegeneration in AT is closely related to the absence or partial lack of the ataxia telangiectasia-mutated (ATM) kinase. ATM is a central player in maintaining cellular homeostasis. Systemic review of the literature reveals a subset of cellular targets hypothesized to count responsible for degeneration in ATM-deficient neurons. Further systematic cliniconeurological, pathoanatomical, and neuroradiological studies are required to understand the structural basis of this neurodegenerative disease. This better understanding has implications for the treatment of AT patients. Second, biochemical and molecular biological studies aimed at deciphering the pathomechanisms of this progressive disorder are necessary for the development of promising future therapies.
Keywords: ataxia telangiectasia; neurodegeneration; neurological symptoms; pathoanatomy; treatment options